Milling-driven nanonization of AsxS100-x alloys from second glass-forming region: The case of lower-crystalline arsenicals (56<x<66) - Shpotyuk, O.; Kozyukhin, S.; Demchenko, P.; Shpotyuk, Y.; Kozdras, A.; Vlček, Miroslav; Kovalskiy, A.; Lukáčová Bujňáková, Z.; Baláž, P.; Mitsa, V.; Veres, M. (My University, 2020)
Competitive intercrystalline phase-transformation and amorphization effects under high-energy mechanical milling are studied in AsxS100-x alloys from low-crystallinity domain (56<x<66) of the second glass-forming region (51<x<66), employing complementary X-ray powder diffraction analysis, micro-Raman scattering spectroscopy, heat flow differential scanning calorimetry and temperature-modulated multifrequency DSC TOPEM® methods. Milling is shown to activate preferential generation of nanosized monoclinic β-As4S4 phase in these AsxS100-x arsenicals at low As content (50<x<60) accompanied by appearance of isocompositional amorphous phase. Principal scenario of milling-driven interphase disproportionality in these arsenicals with high As content (58<x<66) is identified as plastic-crystalline rhombohedral β-As4S3 phase generation supplemented by extraction of As-rich amorphous substance probably of As4S2 composition. Appearance of amorphous a-As4S2 phase with relatively low glass-transition temperature of ~50 °C is supplemented to β-As4S4 polymorph stabilized along with nanostructured plastic-crystalline nc-β-As4S3 phase. Temperature-depressing effects of milling on calorimetric heat-transfer processes are revealed in whole compositional domain of the studied nanoarsenicals.
Mletím indukovaná nanonizace sloučenin AsxS100-x z druhého sklotvorného regionu: případ nízkokrystalických arsenidů (56<x<66)
Keywords: phase transitions; nanonization; arsenic sulphides; X-ray powder diffraction; micro-Raman scattering; differential scanning calorimetry; fázová transformace; nanonizace; sulfid arsenu; rentgenová difrakce; mikro-Raman; diferenciální skenovací kalorimetrie